2011
DOI: 10.1002/eji.201041214
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Listeria vaccine strain by enhanced caspase‐1 activation

Abstract: The immunostimulatory properties conferred by vaccine adjuvants require Caspase-1 for processing of IL-1β and IL-18. Caspase-1 is activated in response to a breach of the cytosolic compartment by microbes and the process is initiated by intracellular pattern recognition receptors within inflammasomes. Listeria monocytogenes is detected in the cytosol by the NLRC4, NLRP3 and AIM2 inflammasomes. NLRC4 is activated by flagellin, and L. monocytogenes evades this detector by repressing flagellin expression. We gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 30 publications
(37 reference statements)
6
45
0
Order By: Relevance
“…In this study we examined the role of inflammasome activation in the development of protective immunity to L. monocytogenes infection. Warren et al recently reported that L. monocytogenes strains engineered to activate the Nlrc4 inflammasome were capable of inducing protective immunity at high immunizing doses (35). In agreement with these findings, we also found that immunization with high doses of L. monocytogenes-L.p.FlaA induced protection from subsequent challenge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study we examined the role of inflammasome activation in the development of protective immunity to L. monocytogenes infection. Warren et al recently reported that L. monocytogenes strains engineered to activate the Nlrc4 inflammasome were capable of inducing protective immunity at high immunizing doses (35). In agreement with these findings, we also found that immunization with high doses of L. monocytogenes-L.p.FlaA induced protection from subsequent challenge.…”
Section: Discussionsupporting
confidence: 92%
“…Both the S. typhimurium study and the present study find attenuation of intracellular bacteria caused by activation of the Nlrc4 inflammasome; however, we find differences in the role that neutrophils play in this process. In agreement with our findings, Warren et al recently reported that L. monocytogenes that hyperactivate the Nlrc4 inflammasome were highly attenuated in vivo by a mechanism independent of IL-1β and IL-18 (35). Understanding how inflammasome activation mediates host defense and how pathogens have overcome these defenses is central to our broader understanding of both mechanisms of pathogenesis and the function of the innate immune system.…”
Section: Discussionsupporting
confidence: 92%
“…Our purified PrgJ and MxiI triggered an increased level of IL-1␤ when transfected into mouse bone marrow-derived macrophages (Fig. 2), similar to the results shown by others that the inner rod proteins were able to increase the amount of IL-1␤ (15)(16)(17).…”
Section: Resultssupporting
confidence: 72%
“…Despite the importance of the inner rod proteins in assembly of the needle complex (3)(4)(5)(6), pathogenesis (11)(12)(13)(14)20), and host immune response (15)(16)(17)(18), little is known about their biophysical and structural properties. Currently, no CD or NMR data has been reported for any T3SS inner rod proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation